ANALISIS KOMPARATIF MATERI MAKSIAT HATI DALAM KITAB SULAM AT-TAUFIQ DAN BUKU AKHLAK TASAWUF - Premuriska Eka Wulandari; Lailatur Rohmah; Mohammad Fahrur Rosi; Maimun (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study comparatively examines the material on the sins of the heart in the book Sulam at Taufiq and the Tasawuf Akhlak textbook for eleventh-grade Islamic senior high school students (MA) and its relevance to students’ moral development. The background of this study is based on the development of digital media that influences adolescents’ psychological conditions and character, showing that morality is not only related to outward behavior but also to inner conditions. This research uses a qualitative approach with a library research method through documentation studies of the kitab, textbooks, and relevant scientific journals, which are then analyzed descriptively and comparatively. The findings show that Sulam at Taufiq presents the material on the sins of the heart in a normative and concise manner while emphasizing tazkiyatun nafs as the core of moral formation through spiritual strengthening and inner awareness. Meanwhile, the Tasawuf Akhlak textbook is arranged more systematically, contextually, and applicatively through daily-life examples and explanations of the social impacts of sins of the heart such as riya’, ujub, hasad, and takabur, making it easier for students to understand.